2019
DOI: 10.1002/jmv.25545
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus antibodies in different human populations of Cameroon

Abstract: Hepatitis E virus (HEV) is a major cause of acute hepatitis worldwide. HEV infection is self-limiting, but fulminant hepatitis may occur with higher mortality rates. The aim of this study was to determine the seroprevalence of the HEV in three different populations in Cameroon and to assess alimentary risk factors of infection. A total of 903 individuals including 450 elderly people, 183 pregnant women, and 270 HIV-infected patients were enrolled during 2009-2015. All sera obtained were tested for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The consumption of these potentially infected water or porcine food can be the means of transmission for HEV. The association between dietary habits and the presence of HEV antibodies has been found in a prior study in the country without a significant value [7]. Some biological studies of these waters and foods should be done to better understand ways of the transmission of the HEV.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The consumption of these potentially infected water or porcine food can be the means of transmission for HEV. The association between dietary habits and the presence of HEV antibodies has been found in a prior study in the country without a significant value [7]. Some biological studies of these waters and foods should be done to better understand ways of the transmission of the HEV.…”
Section: Discussionmentioning
confidence: 89%
“…Bivigou-Mboumba in Gabon in 2017 found a seroprevalence of 3.5% among 762 adults infected with HIV-1 [11]. Feldt obtained a [7]. Demi Sibiro et al obtained a prevalence of 7.5% and 68% of anti-HEV IgM and IgG respectively in Central African Republic among 200 patients living with HIV in 2018 [12].…”
Section: Discussionmentioning
confidence: 98%
“…Other similar studies have shown that HEV IgM seroprevalence is generally between 0-34% in sub-Saharan Africa [17]. The HEV IgM rates detected in other endemic countries were 2.6% in Burkina Faso [18], 10.4% in the Demographic Republic of Congo [12], 38.4% in Niger [19], 22% in Cameroon [20], 0.34% in Algeria [21], and 4.4% in Sudan [22].…”
Section: Discussionmentioning
confidence: 71%
“…However, this does not completely disregard them as putative risk factors, , but may require thorough investigations in Sokode. [31], had also observed that no alimentary risk factors were signi cantly associated with HEV infection in all three populations (elderly people, pregnant women, and HIVinfected patients). But unlike these studies, [34], reported a signi cant correlation between rural area of residence on the one hand and use of fecally contaminated water on the other [35] as well as consumption of pork products [36].…”
Section: Discussionmentioning
confidence: 89%
“…This study is not the rst study to show the high seropositivity to IgM (14.87%) compared with total HEV antibodies (5.62%). A study in Cameroon had already shown high seropositivity to IgM (22.0%) compared with IgG (5.8%) [31]. The high seropositivity to IgM shows that there was possibly an outbreak of HEV infection whose origin was unknown.…”
Section: Discussionmentioning
confidence: 90%